(untitled) (CAHIERS MAGELLANES-NS, 2024)
Electronic voting (e-voting) systems have emerged as a potential solution to enhance the efficiency and accessibility of traditional voting processes. However, ensuring the security, transparency, and integrity of these systems remains a significant challenge. This research paper explores the application of blockchain technology to develop a secure and transparent e-voting system. The proposed e-voting system leverages blockchain's decentralized and immutable nature to address the inherent vulnerabilities in traditional voting mechanisms. By utilizing a distributed ledger, the system ensures tamper-proof record-keeping, preventing unauthorized alterations to the voting data. Smart contracts are employed to automate voting procedures, ensuring accuracy and transparency while reducing the potential for human error. The implementation of cryptographic techniques within the blockchain framework guarantees voter anonymity and confidentiality, protecting sensitive information throughout the voting process. Moreover, the transparency afforded by blockchain enables real-time monitoring of the entire voting process, allowing stakeholders to audit and verify the legitimacy of election results. Through a comprehensive analysis of existing e-voting systems and the integration of blockchain technology, this research aims to provide a robust framework for conducting secure and transparent elections. The findings demonstrate the potential of blockchain-based e-voting systems in overcoming various challenges associated with traditional voting methods, offering a more reliable, efficient, and inclusive approach to democratic decision-making.